2010
DOI: 10.1603/ec10006
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Heat- and Freeze-Killed Oothecae of the American Cockroach (Dictyoptera: Blattidae) as Hosts for an Oothecal Parasitoid, Aprostocetus hagenowii (Hymenoptera: Eulophidae)

Abstract: The objective of this study was to evaluate the suitability of heat- and freeze-killed oothecae of Periplaneta americana (L.) (Dictyoptera: Blattidae) as hosts for parasitoid Aprostocetus hagenowii (Ratzeburg) (Hymenoptera: Eulophidae). The oothecae were subjected to -20, 45, 48, 50, and 55 degrees C at different exposure times (15, 30, 45, and 60 min). The effects of heat- and freeze-killed oothecae on several biological parameters (e.g., parasitism and emergence rates, developmental times, progeny number, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Parasitoid strain and colony maintenance were the same as described in Tee et al (2010). For use in the experiments, 1-to 2-d-old P. americana oothecae were individually subjected to parasitization by a female A. hagenowii in a 2 ml microcentrifuge tube that was tightened with a piece of chiffon cloth to prevent escape of the wasp and allow ventilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasitoid strain and colony maintenance were the same as described in Tee et al (2010). For use in the experiments, 1-to 2-d-old P. americana oothecae were individually subjected to parasitization by a female A. hagenowii in a 2 ml microcentrifuge tube that was tightened with a piece of chiffon cloth to prevent escape of the wasp and allow ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…This step is performed to prevent accidental release of P. americana from unparasitized oothecae into the Þeld (Suiter et al 1998). This combination of minimum temperature and exposure duration to kill oothecae was assumed to have the least effects on the integrity of oothecae as hosts for A. hagenowii (Tee et al 2010). Heat-killed oothecae were individually introduced into a 2 ml microcentrifuge tube that contained a female A. hagenowii.…”
Section: Methodsmentioning
confidence: 99%
“…After multiple generations on B. lateralis , the periodic inclusion of P. americana oothecae in the treatment area may provide an opportunity for A. hagenowii to switch to its preferred host and recover fitness losses. Tee et al (2010) found that A. hagenowii would readily parasitize heat- and cold-killed P. americana oothecae without detrimental effects on emergence, development time, or sex ratio. Thus, killed oothecae of the preferred host could be provided to the released A. hagenowii without risking the introduction of additional pests.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of female progeny under the natural field conditions was 77% [5], and smaller than that under laboratory conditions. Previous studies have demonstrated that it is preferable to have a female biased sex ratio of the parasitoids in biocontrol programs [29,52]. There is often a positive relationship between fitness and body size [46,[53][54][55], and the body size of parasitoids is often positively correlated to their fecundity [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, mass rearing of Aprostocetus parasitoids relies on natural hosts for field release programs, such as mass rearing of Aprostocetus hagenowii Ratzeburg on the American cockroach Periplaneta americana L. for control [29]. To our knowledge, no mass rearing of A. brevipedicellus has been documented.…”
Section: Introductionmentioning
confidence: 99%